PENGARUH GAYA KOMUNIKASI SPORTCASTER TAYANGAN SEPAK BOLA INDONESIA TERHADAP PERUBAHAN SIKAP MASYARAKAT (Studi Pada Followers Aktif Akun Instagram @scoresheet.id) - Endrapta Ibrahim Pramudhiaz, (2022)
The Covid-19 pandemic forced all activities to be suspended. All things involved in sports and professional activities in it. One of them came from soccer, namely Liga 1 2020. The highest soccer competition in Indonesia was forced to stop its competition for up to a year. When the situation finally became favorable, the organizers began to look for ways so that the competition could slowly return to life. To warm up the players who have been playing in the competition for a long time, a pre-season competition for the 2021 Menpora Cup tournament will be held. As the tournament was held for the first time during a pandemic, television stations can certainly contribute by becoming broadcasters. At that time, Emtek Group became the publisher and also brought several well-known sports broadcasters or commentators to enliven the match. The competition started and everything went smoothly. Until finally the Bali United vs PS Sleman match praised the audience for being two camps due to the sportcaster in the match. One side says that the commentator from Valentino Simanjuntak is not worth listening to because of his hyperbolic style that has sparked the viral hashtag #GerakanMuteMassal, on the other hand it says that Valentino Simanjuntak's comments are actually more exciting because of his distinctive style. The theory of mass media effects will be used as a guide in this study. This study will examine the influence of the communication style of Indonesian football broadcasters on changes in people's attitudes, by distributing several questionnaire related to research on several samples from the followers of scoresheet.id Instagram account. The results obtained from this study indicate that the communication style of Indonesian football broadcasters has a strong influence on changes in people's attitudes.